Stress State of Steel Column Strengthened Under Load. (2017) - Ali, Mohamad Al; Kvočák, Vincent; Platko, Peter
Abstract: During the strengthening under load, besides stress caused by external loading, another types of stresses arise in the members. Welding of new parts to the original cross-section creates additional stresses, so called welding stresses, [1, 2 and 3]. Because the strengthening is generally realized under loading, the effect of welding is connected with creation of further strains and stresses from the temporary weakening of original cross-section and shift of the centroid which creates additional bending moments. The paper presents parametric study with some results from ongoing theoretical and experimental research oriented on the strengthening of steel columns under loading.